2021
DOI: 10.1101/2021.05.14.21257006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid Screening of COVID-19 Disease Directly from Clinical Nasopharyngeal Swabs using the MasSpec Pen Technology

Abstract: The outbreak of COVID-19 has created an unprecedent global crisis. While PCR is the gold standard method for detecting active SARS-CoV-2 infection, alternative high-throughput diagnostic tests are of significant value to meet universal testing demands. Here, we describe a new design of the MasSpec Pen technology integrated to electrospray ionization (ESI) for direct analysis of clinical swabs and investigate its use for COVID-19 screening. The redesigned MasSpec Pen system incorporates a disposable sampling de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Apart from the above, some innovative handheld devices were also developed for mass spectrometric analysis in clinics. For example, a handheld device modified based on the MasSpec Pen technology [ 61 ] integrated with ESI-MS was recently reported to successfully analyze lipid profiles in nasopharynx swabs [ 62 ]. It was demonstrated that the lipid profiles could allow identification of SARS-CoV-2 infected patients, as changing in lipid profiles was found upon SARS-CoV-2 infection [ 63 , 64 ].…”
Section: Potential Of Ms For On-site Detection Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the above, some innovative handheld devices were also developed for mass spectrometric analysis in clinics. For example, a handheld device modified based on the MasSpec Pen technology [ 61 ] integrated with ESI-MS was recently reported to successfully analyze lipid profiles in nasopharynx swabs [ 62 ]. It was demonstrated that the lipid profiles could allow identification of SARS-CoV-2 infected patients, as changing in lipid profiles was found upon SARS-CoV-2 infection [ 63 , 64 ].…”
Section: Potential Of Ms For On-site Detection Of Sars-cov-2mentioning
confidence: 99%
“…The solvent is transported from conduit 1 to extract lipids from the swab for 10 s. The lipid-extracted solvent is delivered to the ESI-MS for data acquisition through conduit 2 for 30 s. The total analysis takes about 45 s only (Adapted from Ref. [ 62 ]). …”
Section: Potential Of Ms For On-site Detection Of Sars-cov-2mentioning
confidence: 99%